Method for detecting content of lignosulfonate in cement raw material grinding aid and application thereof

By pretreating and multi-step separation of cement raw material aids, the problem of the impact of impurities in detection is solved, and the accurate detection of lignin sulfonate content is achieved.

CN119510336APending Publication Date: 2025-02-25CHINA RESOURCES CEMENT TECH R & D (GUANGXI) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411444833.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to accurately detect the content of lignin sulfonate in cement raw material aids, and there are problems that impurities affect the detection results.

Method used

The sample to be tested is mixed with the acid and the organic solvent to separate the first solid-liquid, and then the pH of the mixed liquid is adjusted to ≥5, heated and boiled, and barium salt is added for aging reaction. Finally, the liquid to be tested is obtained by the second solid-liquid separation and ultraviolet spectrophotometry detection.

Benefits of technology

Effectively remove impurities in the sample, improve the accuracy of the detection and ensure the reliability of the detection results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005087444200000081
    Figure BDA0005087444200000081
  • Figure BDA0005087444200000111
    Figure BDA0005087444200000111
  • Figure BDA0005087444200000121
    Figure BDA0005087444200000121
Patent Text Reader

Abstract

The invention relates to the field of raw material grinding aid component detection, in particular to a method for detecting the content of lignosulfonate in a cement raw material grinding aid and application of the method. The method for detecting the content of lignosulfonate in the cement raw material grinding aid comprises the following steps: (a) carrying out first solid-liquid separation on a mixed solution containing a to-be-detected sample, acid and an organic solvent, and collecting a precipitate; (b) adjusting the pH value of a mixed solution containing the precipitate and water to be greater than or equal to 5, and then heating to boil to obtain a boiled solution; (c) adding barium salt into the boiled liquid, boiling for a period of time, then carrying out aging reaction, cooling and carrying out second solid-liquid separation to obtain liquid to be detected; and (d) detecting the content of lignosulfonate in the liquid to be detected. According to the method for detecting the content of lignosulfonate in the cement raw material grinding aid, the cement raw material grinding aid is pretreated, and most of impurities interfering a detection result in the raw material grinding aid are removed through pretreatment, so that the detection accuracy is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of raw material grinding aid component detection, and in particular to a method for detecting the content of lignin sulfonate in a cement raw material grinding aid and an application thereof. Background Art

[0002] Lignin sulfonate is a substance commonly used in raw meal grinding aids on the market. It is mainly derived from industrial by-products of the papermaking industry, commonly known as black night. Lignin sulfonate has good dispersibility on calcium raw materials in raw meal. Accurate detection of this content plays an important role in the configuration of cement raw meal and the control of product quality.

[0003] The raw materials of cement raw material grinding aids come from a wide range of sources and have complex components, so it is difficult to determine the content of effective components. The current method for detecting wood sulfonate in cement raw material grinding aids is to directly dissolve the sample to be tested with deionized water. The solubility and stability of the sample during preparation cannot be effectively guaranteed, and the influence of impurities on the test results cannot be effectively avoided, resulting in inaccurate test results and large errors.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a method for detecting the content of lignin sulfonate in a cement raw meal grinding aid and its application. The method for detecting the content of lignin sulfonate in a cement raw meal grinding aid has the advantages of effectively removing impurities in a sample, high detection accuracy, simple method, easy operation, etc.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0007] One aspect of the present invention also relates to a method for detecting the content of lignin sulfonate in a cement raw material grinding aid, comprising the following steps:

[0008] (a) subjecting a mixed solution containing a sample to be tested, an acid and an organic solvent to a first solid-liquid separation, and collecting a precipitate;

[0009] (b) adjusting the pH of the mixed solution containing the precipitate, the acid solution and the alkali solution to ≥5 and then heating to boiling to obtain a boiling solution;

[0010] (c) adding a barium salt to the boiling liquid, boiling for a period of time, performing an aging reaction, cooling, and performing a second solid-liquid separation to obtain a test liquid;

[0011] (d) detecting the content of lignin sulfonate in the test solution.

[0012] The method for detecting the content of lignin sulfonate in cement raw meal grinding aid pretreats the cement raw meal grinding aid, and removes most of the impurities in the raw meal grinding aid that interfere with the detection result through the pretreatment, thereby improving the accuracy of the detection.

[0013] Preferably, the pH of the mixed solution containing the sample to be tested, the acid and the organic solvent is ≤2.

[0014] Preferably, the addition ratio of the sample to be tested and the organic solvent is 0.4-25 g:50 mL.

[0015] Preferably, the acid comprises: HCl and / or HNO3.

[0016] Preferably, the organic solvent comprises at least one of anhydrous ethanol, propanol or methanol.

[0017] Preferably, the acid solution comprises: hydrochloric acid and / or nitric acid.

[0018] Preferably, the mass ratio of the sample to be tested to the barium salt is 0.4-25:1.4-2.6.

[0019] Preferably, the barium salt comprises: barium chloride.

[0020] Preferably, the temperature of the aging reaction is 75-85°C.

[0021] Preferably, the aging reaction time is 1.8 to 2.2 hours.

[0022] Preferably, in step (c), the period of time is 4 to 6 minutes.

[0023] Preferably, the content of lignin sulfonate in the test solution is detected by ultraviolet spectrophotometry.

[0024] Another aspect of the present invention also relates to a quality detection method for cement raw meal grinding aid, including the detection method of lignin sulfonate in the cement raw meal grinding aid.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The method for detecting the content of lignin sulfonate in a cement raw material grinding aid provided by the present invention removes impurities in the raw material grinding aid that have an impact on the ultraviolet spectroscopic detection of lignin sulfonate through pretreatment, fully dissolves the lignin sulfonate in the raw material grinding aid in a test liquid, makes the detection result more accurate, and provides data support for the configuration and effect verification of the raw material grinding aid. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0028] One aspect of the present invention relates to a method for detecting the content of lignin sulfonate in a cement raw material grinding aid, comprising the following steps:

[0029] (a) subjecting a mixed solution containing a sample to be tested, an acid and an organic solvent to a first solid-liquid separation, and collecting a precipitate;

[0030] (b) adjusting the pH of the mixed solution containing the precipitate, the acid solution and the alkali solution to ≥5 (for example, it may be but not limited to at least one of 5, 6, 7, 8, 9 or 10 or a range between any two of them) and then heating it to boiling to obtain a boiled solution;

[0031] (c) adding a barium salt to the boiling liquid, boiling for a period of time, performing an aging reaction, cooling, and performing a second solid-liquid separation to obtain a test liquid;

[0032] (d) detecting the content of lignin sulfonate in the test solution.

[0033] The raw materials of cement raw material grinding aids are widely sourced and the components are complex, so it is difficult to determine the content of effective components. Lignin sulfonate can be dissolved in aqueous solutions of various pH values, but is insoluble in ethanol, acetone and general organic solvents. Dissolving the sample directly with deionized water affects the detection accuracy of lignin sulfonate, and the solubility and stability of the sample during preparation cannot be effectively guaranteed. According to the solubility of lignin sulfonate, the method for detecting the content of lignin sulfonate in cement raw material grinding aid of the present invention pre-treats the cement raw material grinding aid, and removes most of the impurities in the raw material grinding aid that interfere with the detection results through pre-treatment, thereby improving the accuracy of the detection.

[0034] The method comprises the following steps: (a) mixing a sample to be tested, an acid and an organic solvent and filtering the mixture, thereby removing alcohol amine substances and other impurities soluble in the organic solvent in the sample to be tested; (b) the solubility of lignin sulfonate in a strong acid medium increases with increasing pH value, the solubility is maximum when the pH value is 5, and the solubility tends to be flat as the pH value increases, dissolving the filtered product and filter paper in water, and adjusting the pH value to ≥ 5 with sodium hydroxide and hydrochloric acid, thereby fully dissolving the lignin sulfonate in the sample to be tested and improving the accuracy of detection; and (c) adding barium salt to the boiling liquid for aging and filtering, thereby effectively removing sulfate in the sample to be tested.

[0035] Further, the added ratio of the sample to be tested and the organic solvent is 0.4-25 g:50 mL, including but not limited to 0.4 g:50 mL, 1 g:50 mL, 5 g:50 mL, 10 g:50 mL, 15 g:50 mL, 20 g:50 mL or 25 g:50 mL. The sample to be tested and the organic solvent are added in a certain ratio, and the added organic solvent is sufficient to remove most of the alcoholamine substances in the sample to be tested.

[0036] Furthermore, the pH of the mixed solution containing the sample to be tested, the acid and the organic solvent is ≤ 2, including but not limited to any one of 0.1, 0.5, 1, 1.5 or 2 or a range between any two of them.

[0037] Lignin sulfonate may undergo acid precipitation under strong acid conditions, that is, when the pH value is less than or equal to 2, lignin sulfonate is insoluble in aqueous solution and ethanol solution. A certain amount of acid is added to the mixed solution of the organic solvent and the sample to be tested, and the pH of the entire system is controlled below 2. Then, filtration is performed to effectively remove alcoholamine substances and other impurities in the sample to be tested.

[0038] Furthermore, the acid includes but is not limited to: HCl and / or HNO3.

[0039] Furthermore, the acid is added in the form of a solution, and the concentration of the acid solution is 1 to 2 g / mL, including but not limited to any point value of 1 g / mL, 1.2 g / mL, 1.4 g / mL, 1.6 g / mL, 1.8 g / mL or 2 g / mL or a range value between any two of them.

[0040] Furthermore, the organic solvent includes but is not limited to: at least one of anhydrous ethanol, propanol or methanol.

[0041] Furthermore, the acid solution includes: hydrochloric acid and / or nitric acid.

[0042] Furthermore, the alkali solution includes: sodium hydroxide.

[0043] Furthermore, the mass ratio of the sample to be tested and the barium salt is 0.4-25:1.4-2.6, including but not limited to 0.4:2.6, 1:2.4, 5:2.2, 10:2.0, 15:1.8, 20:1.6 or 25:1.4. The sample to be tested and the barium salt are added in a certain mass ratio, which can fully remove the sulfate in the sample to be tested, while avoiding the waste of reagents caused by adding excessive barium salt and the introduction of new impurities.

[0044] Furthermore, the barium salt includes but is not limited to: barium chloride.

[0045] Further, the barium salt is added dropwise in the form of a solution, the concentration of the barium salt solution is 95-105 g / L (for example, it can be but not limited to any one of 95 g / L, 97 g / L, 99 g / L, 101 g / L, 103 g / L or 105 g / L, or a range between any two of them), and the dropping speed of the barium salt solution is 0.1-0.3 mL / s (for example, it can be but not limited to any one of 0.1 mL / s, 0.2 mL / s or 0.3 mL / s, or a range between any two of them).

[0046] Further, in step (c), the period of time is 4 to 6 minutes, including but not limited to any one of 4 minutes, 4.5 minutes, 5 minutes, 5.5 minutes or 6 minutes or any range between two of them. After a period of boiling, the components in the system are fully mixed, which is conducive to the full progress of the aging reaction.

[0047] Furthermore, the temperature of the aging reaction is 75-85°C, including but not limited to any one of 75°C, 77°C, 79°C, 81°C, 83°C or 85°C or a range between any two of them.

[0048] Furthermore, the aging reaction time is 1.8 to 2.2 hours, including but not limited to any one of 1.8 hours, 1.9 hours, 2.0 hours, 2.1 hours or 2.2 hours or a range between any two of them.

[0049] Carrying out aging reaction under certain temperature and time conditions can ensure that the barium sulfate is aged completely, fully remove the sulfate in the sample to be tested, and improve the accuracy of the test.

[0050] Furthermore, the content of lignin sulfonate in the test solution is detected by ultraviolet spectrophotometry.

[0051] Furthermore, the detection wavelength of the ultraviolet spectrophotometry is 280 nm.

[0052] Furthermore, the first solid-liquid separation is performed by medium-speed quantitative filter paper filtration.

[0053] Furthermore, the second solid-liquid separation is performed by rapid quantitative filter paper filtration.

[0054] Furthermore, the sample to be tested is dried to remove water and volatile impurities in the sample.

[0055] In some specific embodiments, the method for detecting the content of lignin sulfonate in cement raw meal grinding aid comprises the following steps:

[0056] 1. Weigh 0.4-25g of sample and dry it in an oven at 100-110°C (for example, but not limited to, any one of 100°C, 103°C, 105°C, 108°C or 110°C or a range between any two of them), take it out, add 50mL of anhydrous ethanol, stir and dissolve it, add hydrochloric acid with a concentration of 1-2g / mL, control the pH value of the mixed solution to 2 or below, filter it with medium-speed quantitative filter paper, and rinse the filter paper with anhydrous ethanol;

[0057] 2. Place the filter paper in 90-110 mL (for example, but not limited to any one of 90 mL, 95 mL, 100 mL, 105 mL or 110 mL or a range between two of them) of deionized water, dropwise add a sodium hydroxide solution having a concentration of 35-45 g / L (for example, but not limited to any one of 35 g / L, 37 g / L, 39 g / L, 41 g / L, 43 g / L or 45 g / L or a range between two of them) and a hydrochloric acid solution having a concentration of 5-7 mol / L, and boil after controlling the pH value to 5 or above;

[0058] 3. Add 15-25 ml (for example, but not limited to, any one of 15 ml, 17 ml, 19 ml, 21 ml, 23 ml or 25 ml or any range between two) of a barium chloride solution with a concentration of 95-105 g / L dropwise under a slightly boiling state, at a rate of 0.1-0.3 mL / s, and boil for 4-6 min. Transfer the solution to a volumetric flask and place it in a constant temperature water bath at 75-85 ° C for 1.8-2.2 h.

[0059] 4. Take out and cool to room temperature, add water to the scale and shake well, filter with quantitative rapid filter paper to prepare a solution with a sample concentration of 10 to 100 mg / mL (for example, but not limited to, any point value of 10 mg / mL, 20 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL or 100 mg / mL or a range value between any two);

[0060] 5. Preparation of standard curve: Take an appropriate amount of lignin sulfonate standard, add an appropriate amount of deionized water to dilute, and prepare a standard solution with a concentration of 10-100 mg / L (for example, but not limited to, any point value of 10 mg / mL, 20 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL or 100 mg / mL or a range value between any two);

[0061] 6. Determination by ultraviolet spectrophotometry: Place the sample solution and standard solution into an ultraviolet spectrophotometer respectively, measure their absorbance at 280 nm, and calculate the content of lignin sulfonate in the sample according to the standard curve.

[0062] Another aspect of the present invention also relates to a quality detection method for cement raw meal grinding aid, including the detection method of lignin sulfonate in the cement raw meal grinding aid.

[0063] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0064] Example 1

[0065] The method for detecting the content of lignin sulfonate in cement raw material grinding aid provided in this embodiment comprises the following steps:

[0066] 1. Take an appropriate amount of lignin sulfonate standard, add an appropriate amount of deionized water to dilute, prepare a standard solution with a concentration of 10-100 mg / L, use water as the reference solution, measure its absorbance at 280 nm, and obtain the standard curve equation y=0.0099X+0.0025, R 2 is 0.9998, y is the absorbance, and X is the concentration of lignin sulfonate;

[0067] 2. Weigh four samples to be tested respectively, with different weights of each sample, namely 0.4890g, 20.2201g, 15.2866g and 25.2828g. Put each sample to be tested into four different 400ml beakers and put them into a 105℃ oven for drying. Take out and add 50mL of anhydrous ethanol to each sample to be tested, stir and dissolve, add hydrochloric acid with a concentration of 1.19g / mL, control the pH value to 2, filter with medium-speed quantitative filter paper, and rinse with anhydrous ethanol;

[0068] 3. Take the filter paper and add the sample into a 400ml beaker, add 100mL deionized water to dissolve, add 40g / L sodium hydroxide and 6mol / L hydrochloric acid solution dropwise, control the pH value to 5 and boil;

[0069] 4. Under the slightly boiling state, add 20 ml of 100 g / L barium chloride solution at a speed of 0.2 mL / s, and boil for 5 min. Transfer the solution in the beaker to a 500 mL volumetric flask, place it in a constant temperature water bath at 80 ° C and let it stand for 2 hours; take it out and cool it to room temperature, add water to the scale and shake it well, filter it with quantitative rapid filter paper to obtain the test solution;

[0070] 5. Use an ultraviolet spectrophotometer to measure the absorbance of the test solution at 280 nm, and calculate the content of lignin sulfonate in the sample based on the standard curve equation y=0.0099X+0.0025 and the diluted volume.

[0071] Table 1 Detection results of lignin sulfonate content in the sample to be tested in Example 1

[0072]

[0073] Example 2

[0074] The method for detecting the content of lignin sulfonate in cement raw material grinding aid provided in this embodiment comprises the following steps:

[0075] 1. Same as Example 1;

[0076] 2. Weigh 2.6854g of the sample to be tested into a 400ml beaker and place it in a 105℃ oven for drying. Take it out and add 50mL of anhydrous ethanol to stir and dissolve. Add hydrochloric acid with a concentration of 1.19g / mL and control the pH value to 1.8. Filter with medium-speed quantitative filter paper and rinse with anhydrous ethanol.

[0077] 3. Take the filter paper and add the sample into a 400ml beaker, add 100mL deionized water to dissolve, add 40g / L sodium hydroxide and 5mol / L hydrochloric acid solution dropwise, control the pH value to 6 and boil;

[0078] 4. In a slightly boiling state, add 15 ml of 105 g / L barium chloride solution at a rate of 0.2 mL / s, and boil for another 4 min. Transfer the solution in the beaker to a 500 mL volumetric flask, and place it in a constant temperature water bath at 85 °C for 1.8 hours; take it out and cool it to room temperature, add water to the scale and shake well, and filter it with quantitative rapid filter paper to obtain the test solution;

[0079] 5. Use an ultraviolet spectrophotometer to measure the absorbance of the test solution at 280 nm, and calculate the content of lignin sulfonate in the sample based on the standard curve equation y=0.0099X+0.0025 and the diluted volume.

[0080] Example 3

[0081] The method for detecting the content of lignin sulfonate in cement raw material grinding aid provided in this embodiment comprises the following steps:

[0082] 1. Same as Example 1;

[0083] 2. Weigh 5.7896g of the sample to be tested into a 400ml beaker and place it in a 105℃ oven for drying. Take it out and add 50mL of anhydrous ethanol to stir and dissolve. Add hydrochloric acid with a concentration of 1.19g / mL and control the pH value to 1.4. Filter with medium-speed quantitative filter paper and rinse with anhydrous ethanol.

[0084] 3. Take the filter paper and add the sample into a 400ml beaker, add 100mL deionized water to dissolve, add 40g / L sodium hydroxide and 7mol / L hydrochloric acid solution dropwise, control the pH value to 7 and boil;

[0085] 4. Under the slightly boiling state, add 18 ml of 103 g / L barium chloride solution at a speed of 0.2 mL / s, and boil for another 6 min. Transfer the solution in the beaker to a 500 mL volumetric flask, place it in a constant temperature water bath at 83 °C and let it stand for 1.9 hours; take it out and cool it to room temperature, add water to the scale and shake it well, filter it with quantitative rapid filter paper to obtain the test solution;

[0086] 5. Use an ultraviolet spectrophotometer to measure the absorbance of the test solution at 280 nm, and calculate the content of lignin sulfonate in the sample based on the standard curve equation y=0.0099X+0.0025 and the diluted volume.

[0087] Example 4

[0088] The method for detecting the content of lignin sulfonate in cement raw material grinding aid provided in this embodiment comprises the following steps:

[0089] 1. Same as Example 1;

[0090] 2. Weigh 12.4587g of the sample to be tested into a 400ml beaker and place it in a 105℃ oven for drying. Take it out and add 50mL of anhydrous ethanol to stir and dissolve. Add hydrochloric acid with a concentration of 1.19g / mL and control the pH value to 1.0. Filter with medium-speed quantitative filter paper and rinse with anhydrous ethanol.

[0091] 3. Take the filter paper and add the sample into a 400ml beaker, add 100mL deionized water to dissolve, add 40g / L sodium hydroxide and 6mol / L hydrochloric acid solution dropwise, control the pH value to 8 and boil;

[0092] 4. In a slightly boiling state, add 23 ml of 98 g / L barium chloride solution at a rate of 0.2 mL / s, and boil for 5 min. Transfer the solution in the beaker to a 500 mL volumetric flask, place it in a 78 ° C constant temperature water bath and let it stand for 2.1 hours; take it out and cool it to room temperature, add water to the scale and shake it well, filter it with quantitative rapid filter paper to obtain the test solution;

[0093] 5. Use an ultraviolet spectrophotometer to measure the absorbance of the test solution at 280 nm, and calculate the content of lignin sulfonate in the sample based on the standard curve equation y=0.0099X+0.0025 and the diluted volume.

[0094] Example 5

[0095] The method for detecting the content of lignin sulfonate in cement raw material grinding aid provided in this embodiment comprises the following steps:

[0096] 1. Same as Example 1;

[0097] 2. Weigh 23.2458g of the sample to be tested into a 400ml beaker and place it in a 105℃ oven for drying. Take it out and add 50mL of anhydrous ethanol to stir and dissolve. Add hydrochloric acid with a concentration of 1.19g / mL and control the pH value to 0.5. Filter with medium-speed quantitative filter paper and rinse with anhydrous ethanol.

[0098] 3. Take the filter paper and add the sample into a 400ml beaker, add 100mL deionized water to dissolve, add 40g / L sodium hydroxide and 6mol / L hydrochloric acid solution dropwise, control the pH value to 9 and boil;

[0099] 4. In a slightly boiling state, add 25 ml of 95 g / L barium chloride solution at a rate of 0.2 mL / s, and boil for 5 min. Transfer the solution in the beaker to a 500 mL volumetric flask, place it in a 75 ° C constant temperature water bath and let it stand for 2.2 hours; take it out and cool it to room temperature, add water to the scale and shake it well, filter it with quantitative rapid filter paper to obtain the test solution;

[0100] 5. Use an ultraviolet spectrophotometer to measure the absorbance of the test solution at 280 nm, and calculate the content of lignin sulfonate in the sample based on the standard curve equation y=0.0099X+0.0025 and the diluted volume.

[0101] Table 2 Test results of lignin sulfonate content in samples tested in Examples 2 to 5

[0102]

[0103] Comparative Example 1

[0104] The method for detecting the content of lignin sulfonate in the cement raw material grinding aid provided in this comparative example comprises the following steps:

[0105] Weigh several samples into a 400ml beaker and add 100ml deionized water to dissolve. The weighed mass of each sample is shown in Table 3. Transfer the solution in the beaker to a 500ml volumetric flask, add water to the scale and shake well to prepare the test solution. Use an ultraviolet spectrophotometer to measure its absorbance at 280nm. Calculate the content of lignin sulfonate in the sample based on the standard curve equation y=0.0099X+0.0025 and the diluted volume.

[0106] Table 3 Comparative Example 1 Test results of lignin sulfonate content in the tested samples

[0107]

[0108] The sample to be tested in Comparative Example 1 was not pretreated, and the test solution contained more impurities, resulting in a large error in the calibration result.

[0109] Comparative Example 2

[0110] The method for detecting the content of lignin sulfonate in the cement raw material grinding aid provided in this comparative example comprises the following steps:

[0111] Weigh several samples into a 400ml beaker and add 100ml deionized water to dissolve. The weighed mass of each sample is shown in Table 4. Add a 6mol / L hydrochloric acid solution, control the pH value to 5 and then boil. Add 20ml of a 100g / L barium chloride solution under slight boiling at a speed of 0.2ml / s, and boil for 5min. Transfer the solution in the beaker to a 500ml volumetric flask, place it in a constant temperature water bath at 80℃ and let it stand for 2 hours; take it out and cool it to room temperature, add water to the scale and shake it well, filter it with quantitative rapid filter paper, prepare it into a test solution, and measure its absorbance at 280nm with an ultraviolet spectrophotometer. Calculate the content of lignin sulfonate in the sample according to the standard curve equation y=0.0099X+0.0025 and the diluted volume.

[0112] Table 4 Comparative Example 2 Test results of lignin sulfonate content in the tested samples

[0113]

[0114] In Comparative Example 2, the samples were not dried, and the samples to be tested were not treated with acid and organic solvent. The test solution contained more impurities, resulting in a large error in the calibration results.

[0115] Comparative Example 3

[0116] The method for detecting the content of lignin sulfonate in the cement raw material grinding aid provided in this comparative example comprises the following steps:

[0117] Weigh 0.5g of the sample into a 400ml beaker and place it in a 105℃ oven for drying. Take it out and add 50mL of anhydrous ethanol to stir and dissolve. Add hydrochloric acid with a concentration of 1.19g / mL, drop 40g / L sodium hydroxide and 6mol / L hydrochloric acid solution, and control the pH value between 1-6. The specific pH is shown in Table 5. Filter with medium-speed quantitative filter paper, rinse with anhydrous ethanol, take the filter paper and add the sample into a 400ml beaker, add 100mL of deionized water to dissolve, boil, and drop 20ml of 1% 00g / L barium chloride solution, the speed is controlled at 0.2mL / s, and then boiled for 5min, the solution in the beaker is transferred to a 500mL volumetric flask, placed in a constant temperature water bath at 80℃ and allowed to stand for 2 hours; taken out and cooled to room temperature, water is added to the scale and shaken, filtered with quantitative rapid filter paper, prepared into the test solution, and its absorbance at 280nm is measured with an ultraviolet spectrophotometer, and the content of lignin sulfonate in the sample is calculated according to the standard curve equation y=0.0099X+0.0025 and the diluted volume.

[0118] Table 5 Test results of lignin sulfonate content in the samples to be tested in Comparative Example 3

[0119]

[0120] It can be seen from Comparative Example 3 that the solubility of lignin sulfonate is affected by pH and can be dissolved in an aqueous solution with a pH value of 5 or above.

[0121] Comparative Example 4

[0122] The method for detecting the content of lignin sulfonate in the cement raw material grinding aid provided in this comparative example comprises the following steps:

[0123] Weigh several samples into a 400ml beaker and put them into a 105℃ oven for drying. The weighed mass of each sample is shown in Table 6. Take them out and add 50mL of anhydrous ethanol to stir and dissolve. Add hydrochloric acid with a concentration of 1.19g / mL, control the pH value to 2, filter with medium-speed quantitative filter paper, rinse with anhydrous ethanol, take the filter paper and add the sample into a 400ml beaker, add 100mL of deionized water to dissolve, add sodium hydroxide with a concentration of 40g / L and hydrochloric acid solution with a concentration of 6mol / L, control the pH value to 5, add water to the scale and shake well, filter with quantitative rapid filter paper, prepare the test solution, and measure its absorbance at 280nm with an ultraviolet spectrophotometer. Calculate the content of lignin sulfonate in the sample according to the standard curve equation y=0.0099X+0.0025 and the diluted volume.

[0124] Table 6 Comparative Example 4 Test results of lignin sulfonate content in the tested samples

[0125]

[0126] It can be seen from Comparative Example 4 that the barium salt was not used to remove impurities from the sample to be tested, resulting in errors in the test results.

[0127] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for detecting the content of lignin sulfonate in cement raw material grinding aid, characterized in that: The following steps are involved: (a) subjecting a mixed solution containing a sample to be tested, an acid and an organic solvent to a first solid-liquid separation, and collecting a precipitate; (b) adjusting the pH of the mixed solution containing the precipitate, the acid solution and the alkali solution to ≥5 and then heating to boiling to obtain a boiling solution; (c) adding a barium salt to the boiling liquid, boiling for a period of time, performing an aging reaction, cooling, and performing a second solid-liquid separation to obtain a test liquid; (d) detecting the content of lignin sulfonate in the test solution.

2. The method for detecting the content of lignin sulfonate in cement raw material grinding aid according to claim 1, characterized in that: The pH of the mixed solution containing the sample to be tested, the acid and the organic solvent is ≤2.

3. The method for detecting the content of lignin sulfonate in cement raw meal grinding aid according to claim 2, characterized in that: The addition ratio of the sample to be tested and the organic solvent is 0.4-25 g:50 mL.

4. The method for detecting the content of lignin sulfonate in cement raw material grinding aid according to claim 3, characterized in that: The acid includes: HCl and / or HNO3; And / or, the organic solvent includes at least one of anhydrous ethanol, propanol or methanol.

5. The method for detecting the content of lignin sulfonate in cement raw material grinding aid according to claim 1, characterized in that: The acid solution includes: hydrochloric acid and / or nitric acid.

6. The method for detecting the content of lignin sulfonate in cement raw material grinding aid according to claim 1, characterized in that: The mass ratio of the sample to be tested to the barium salt is 0.4-25:1.4-2.

6.

7. The method for detecting the content of lignin sulfonate in cement raw material grinding aid according to claim 6, characterized in that: The barium salt includes: barium chloride.

8. The method for detecting the content of lignin sulfonate in cement raw material grinding aid according to claim 1, characterized in that: Includes at least one of the following technical features: (1) The temperature of the aging reaction is 75 to 85° C.; (2) The aging reaction time is 1.8 to 2.2 hours; (3) In step (c), the period of time is 4 to 6 minutes.

9. The method for detecting the content of lignin sulfonate in cement raw material grinding aid according to claim 1, characterized in that: The content of lignin sulfonate in the test solution is detected by ultraviolet spectrophotometry.

10. A quality detection method for cement raw meal grinding aid, characterized in that: The invention comprises the method for detecting lignin sulfonate in cement raw material grinding aid according to any one of claims 1 to 9.